Preattentive Processing of Numerical Visual Information - Hesse, Philipp N.; Schmitt, Constanze; Klingenhoefer, Steffen; Bremmer, Frank (Frontiers in Human Neuroscience, 2017)
Humans can perceive and estimate approximate numerical information, even when accurate counting is impossible e.g. due to short presentation time. If the number of objects to be estimated is small, typically around one to four items, observers are able to give very fast and precise judgments with high confidence – an effect that is called subitizing. Due to its speed and effortless nature subitizing has usually been assumed to be preattentive, putting it into the same category as other low level visual features like color or orientation. More recently, however, a number of studies have suggested that subitizing might be dependent on attentional resources. In our current study we investigated the potentially preattentive nature of visual numerical perception in the subitizing range by means of EEG. We presented peripheral, task irrelevant sequences of stimuli consisting of a certain number of circular patches while participants were engaged in a demanding, non-numerical detection task at the fixation point drawing attention away from the number stimuli. Within a sequence of stimuli of a given number of patches (called ‘standards’) we interspersed some stimuli of different numerosity (‘oddballs’). We compared the evoked responses to visually identical stimuli that had been presented in two different conditions, serving as standard in one condition and as oddball in the other. We found significant visual mismatch negativity (vMMN) responses over parieto-occipital electrodes. In addition to the ERP analysis, we performed a time-frequency analysis to investigate whether the vMMN was accompanied by additional oscillatory processes. We found a concurrent increase in evoked theta power of similar strength over both hemispheres. Our results provide clear evidence for a preattentive processing of numerical visual information in the subitizing range.